Mind the Risk: Exploring What Drives Cybersecurity Readiness Among Digital Consumers in Sarawak - Tang, Maximus Balla; Andam, Jessica Lyn; Suzali, Mohd Ngah Ismail (Journal of Social Transformation and Regional Development, 2025)
Sarawak is undergoing a significant digital transition with the aim of becoming a fully integrated and digitally driven economy by 2030. However, as digital device usage increases, consumers are confronted with a variety of cybersecurity concerns. The main objective of this research is to assess the psychological factors influencing digital consumers’ readiness to engage with cybersecurity measures in Sarawak’s digital transformation. To accomplish this, the study expands the Unified Theory of Acceptance and Use of Technology (UTAUT) model to provide a comprehensive framework to measure cybersecurity readiness. A quantitative research approach was employed, with a sample size of 400 respondents. The study employed SmartPLS 4.0 to conduct data analysis, utilizing its capabilities for Partial Least Squares Structural Equation Modeling (PLS-SEM). The study finds that six out of ten hypotheses were supported, with performance expectancy, facilitating conditions, perceived risk, and cybersecurity awareness significantly influencing consumers’ behavioural intention to adopt cybersecurity measures. Additionally, behavioural intention and cybersecurity awareness were found to be significant factors in determining cybersecurity readiness. As Sarawak undergoes digital transformation, understanding the factors that affect cybersecurity readiness is crucial to ensure the population is prepared for the risks and challenges of new technologies. This study makes three key contributions: (1) It extends the UTAUT model by adding cybersecurity behaviours, offering a clearer understanding of digital consumers’ cybersecurity readiness. (2) It offers valuable insights for policymakers in Sarawak. (3) The findings also provide valuable guidance for businesses to tailor their digital products and cybersecurity-related services to better meet the readiness levels and needs of consumers in Sarawak’s evolving digital landscape.